Partido dos Trabalhadores: da ruptura com a lógica da diferença à sustentação da ordem - Garcia, Cyro (2008)
This work shows the results of a research about the transformations inside the Workers Party (PT Partido dos Trabalhadores) along the decade of the 90's. These transformations are consequences of the process of bureaucratization that reaches the Party, and that has its origins in the electoral successes, taking it to a greater integration to the bourgeois state apparatus. This process has got worse when the Party trade unionists become part of management organs of the financial capital, in particular the pension funds that had a fundamental role on the implementation of the privatization politics of the Fernando Henrique Cardoso Government. The main purpose of this work is to analyze how these transformations, resulting of the process of bureaucratization, cause a significant change in its theoretical-programmatical ideas, and in the Party praxis itself changing from a confrontation party with the neoliberal order to a supporting party to this same order. The PT change in its relation with the social movements is analyzed in this thesis, focusing in the role performed by the Unique Workers Central (CUT Central Única dos Trabalhadores), that in its origins was an important instrument of the workers struggle, and nowadays it became a link with interests of Lula's Government. The main hypothesis is that the bureaucratization moved the Party away from its original bases and changed it into a supporting of the neoliberal order.